IMPLEMENTASI METODE QIRO’ATI DALAM PEMBELAJARAN AL QUR’AN DI KELAS XI SMAN 1 NANSABARIS KABUPATEN PADANG PARIAMAN - Putri Dynanti; Khairuddin, Alimir, Januar (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this research is to describe all matters related to the implementation of the Qiro'ati method in learning the Qur'an in class XI SMAN 1 Nansabaris Kabupaten Padang Pariaman, both the use of the Qiroati method and the factors that hinder and support learning the Qur'an using the Qiro' method. The research method used is a qualitative descriptive method that describes events that occur in the field or research that tries to reveal and describe a phenomenon or event that is developing at this time. This research is descriptive qualitative in the form of written or spoken words from people and observed behavior. The data collection technique used is observation, which is a data collection technique by observing. Interview is a data collection technique through question and answer process, both oral and written. Documentation is a way of collecting data through written remains, archives, and books related to research. The results showed that the application of the qiro'ati method in learning the Qur'an in class XI SMAN 1 Nansabaris, Padang Pariaman Regency, the steps taken included planning, implementation and evaluation. Al- Qur'an learning strategies that are used individual classics and read-see classics.